A contribution to the linguistic history of the língua geral amazônica - Rodrigues, Ayron Dall'Igna; Cabral, Ana Suelly Arruda Câmara (ALFA: Revista de Linguística, 2011)
This paper demonstrates that the changes undergone by Língua Geral Amazônica over 300 years, although it had been exposed to external interference from the Portuguese language and a number of indigenous languages, its development has been gradual without a breakdown on its transmission. This accounts for its genetic origin, according to the principles underlying the Comparative Method and the theoretical model proposed by Thomason and Kaufman (1988). This approach brings evidence against the claim that Língua Geral Geral Amazônica is a creole language neither a language developed by the seventeenth century Jesuit missionaries. Therefore, this paper contributes to the viewing of Língua Geral Amazônica is a version of the Tupinambá language which developed outside the Tupinambá villages but maintaining its genetic relations with the subbranch III of the Tupí-Guaraní linguistic family, together with Tupinambá, Tupí Antigo and the Língua Geral Paulista, as proposed by Rodrigues (1985), in his internal classification of that family.